Client-Identified Impacts of Helpful and Hindering Events in Psychotherapy: A Qualitative Meta-analysis - Ladmanová, Michaela; Řiháček, Tomáš; Timulak, Ladislav (Psychotherapy research, 2022)
OBJECTIVE: Understanding the client perspective is important for the provision of psychotherapy. The significant events paradigm, within which clients report on the most significant events of a therapy session immediately after the session, represents a useful means to explore clients' in-session experience. METHOD: The aim of this study was to investigate what types of client-identified impacts are reported in qualitative studies on helpful and hindering events in psychotherapy. Seventeen primary studies focusing on client-identified helpful and hindering events were identified through database searches and subsequent manual searches. The data were subjected to qualitative meta-analysis. RESULTS: The descriptions of event impacts were classified into 12 helpful (e.g., gaining a new perspective on the self; feeling heard, understood, and accepted; and feeling engaged in the therapeutic process) and eight hindering (e.g., lacking guidance from the therapist and feeling emotionally overwhelmed) impact meta-categories. CONCLUSION: The findings provide an update to a previous meta-analysis by identifying several new categories of helpful event impacts and by categorizing hindering event impacts.
Keywords: Emotions; psychoterapie; lidé; emoce; Psychotherapy; Qualitative Research; kvalitativní výzkum; Humans; Professional-Patient Relations; vztahy mezi zdravotnickým pracovníkem a pacientem